Active English workbook 3 (Singapore: Scholastic Education International Private Limited, 2014)
"Active English Workbook 3" is designed for intermediate learners to enhance their English language skills. It focuses on developing reading, writing, listening, and speaking abilities through engaging activities and exercises. The workbook includes grammar explanations, vocabulary building, and practice tasks that promote active participation. Each unit is structured to encourage critical thinking and reinforce language concepts in a fun and interactive way, making it suitable for both classroom use and self-study.
"Active English Workbook 3" serves as a valuable resource for learners looking to improve their English proficiency. It emphasizes a hands-on approach, encouraging students to actively engage with the material through various exercises. The workbook is structured to build on previous knowledge, making it ideal for those who have a foundational understanding of English.
Keywords: Language Acquisition; English Proficiency; Intermediate English